Development and validation of HPTLC method for simultaneous estimation of bioactive components in combined extracts of three hepatoprotective plants. Issue 7 (9th May 2021) - Mehta, Sharuti; Sharma, Anil Kumar; Singh, Rajesh K.
Abstract: Picroside-I, andrographolide and silybin exhibit manifold biological activities, present as bioactive components in Picrorhiza kurroa (roots), Andrographis paniculata (aerial parts) and Silybum marianum (seeds), respectively. A validated HPTLC method was developed for the simultaneous determination of picroside-I, andrographolide and silybin in the combined hydroalcoholic extract of the plants as per ICH guidelines. On silica gel F254 HPTLC plates, the combined hydroalcoholic extract of plants and standard solutions were applied. The plates were run in twin chamber consisting n-butanol: glacial acetic acid: water (6:1:3, v/v/v ) as a mobile phase and documented at 254 and 366 nm using Camag TLC scanner III with WinCATS software. The analysis revealed that a good linear relationship was established between response (peak area) and amount in the range of 60–600 ng/spot. The LOD (ng/spot) and LOQ (ng/spot) for estimation of picroside-I, andrographolide and silybin were found to be 15.089, 21.969, 25.702 and 45.725, 66.573, 77.885, respectively. Recovery experiments showed 97.75–103.74%, 99.75–101.12% and 98.96–101.69% for picroside-I, andrographolide and silybin, respectively. The HPTLC method showed good linearity, recovery and high precision of all the three bioactive components, which can be applied for the routine analysis of polyherbal formulations containing these plants as their ingredients. Graphical abstract: UF0001